Malaria Morbidity Prediction Scenario in Indonesia - Tria Anggita Hafsari; Yulinda Nurul Aini; Fuat Edi Kurniawan (Deputy of Social Sciences and Humanities, the Indonesia Institute of Sciences (LIPI), 2019)
Governments commitment in eradicating malaria has been realized in Malaria elimination program. The program aims to reduce Malaria case to zero in 2030. Starting from 2011, Indonesia suffered a drop in APIs value from 1,75 to 0,84. Despite the numerous drop in Malaria cases, some regions are still suffering from large major outbreaks especially in eastern Indonesia. WHO declares that Indonesia is a country at risk of malaria, because of the high rates of malaria morbidity. The aims of this paper is to predict the trend of malaria morbidity with the API variable value of each province in Indonesia. The method used in this research is probabilistic method using extrapolation trends and ARIMA (Autoregressive Integrated Moving Average) using variation percentage of training and testing data to obtain the best prediction method. Result of this article is API value scenario in Indonesia up to 2030. Based on the analysis result, the best method to predict the value of API is exponential growth method because it has the smallest MAPE value, which is 38.48 using 80% training data and 20% testing data. The prediction results show that from year 2018 to 2030, the value of API will decrease from 0.45 to 0.016.